Comprometimento e entrincheiramento com a carreira de enfermeiros: uma análise dos vínculos em instituições hospitalares públicas e privadas - Lima, Mauren Pimentel (2013)
Individuals have become their own builders of conditions for their employability and responsible for their professional development (Evans, 1996; SORJ, 2000). Workers committed to their career have assumed considerable importance as essential focus (BLAU; COHEN, 2003). The career commitment sets up as a "psychological link between an employee and his career, which is based on affective relationship" (Lee et al., 2000, p. 800). On the other hand, with an unrest and unsteadiness on the today s labor market compromise the stability of their careers resulting in entrenchment. This bond is characterized by immobility of the individual with the adaptation of new opportunities in their career or motivation to change (CARSON et al., 1995). These linkages arise from the motivation of individuals, being relevant to analyze the practical implications career (CARSON et al., 1996). It is evident that the universe of hospital work consists of a congregation of knowledge, technology and diversity in its infrastructure which generates a peculiar division of labor in both technical and social criteria (PINE et al., 2013). It is noteworthy, in this context, the nurse who is responsible for the management of health services to ensure the quality of care provided to patients (FELI et al., 2011; MACHADO et al., 2012). Faced with the reality described, this study was conducted in order to analyze the prevalence of the types of bonds - commitment and entrenchment within the career of hospital nurses in public and private institutions. It was conducted a descriptive, explanatory and exploratory research with use of quantitative methodologies. Study participants totaled 237 nurses in public and private hospitals of cities located in the state of Rio Grande do Sul. A semi-structured questionnaire was applied consisting of questions covering socio-demographic, occupational and links about the career - commitment to the entrenchment of career Blau (1985), Carson and Bedeian (1994) and Carson et al. (1995). Data obtained were analyzed using descriptive statistics, nonparametric tests and correlations. It was evidenced in the general characterization of the profile the predominance of women professionals (89.36%), of public hospitals (65.82%), aged 30 to 39 years (37.13%), married (50.43%) parents (65.11%), averaging two children (42.95%), up to 10-year career (38.98%), 6 to 10 minimum wages (52.63%) and specialists (70.98 %). Overall we identified high levels of commitment (70.46%) and low entrenchment with the career (91.98%). It is noteworthy that high levels of commitment are associated to high identification with planning a career as a nurse. When comparing the nurses in the study by type of institution it was found that professionals in the private sector (85.19%) are more affected than those of public hospitals (80.77%). The correlations, in general, were positive and moderate for the dimensions of career commitment, i.e., identity (r = 0.6219, p = 0.001), planning (r = 0.6219, p = 0.0001) and resilience (r = 0.5274, p = 0.001). It was obtained for the entrenchment with career moderate and negative correlation to the size of alternatives (r = -0.4104, p = 0.001). Therefore, it is expected that the realization of this study will serve as reflection for this category of professionals who work in the hospital motivating improvements in health care management and assistance in patient caring.